ORGANIZE AND OPTIMIZE MULTIPLE INTELLIGENCES OF STUDENTS - Islamiyah Islamiyah; Musohihul Hasan; Nail Shankar (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2022)
Intelligence, experts generally define it through a learning theory approach, a neurobiological theory approach, a theoretical approach psychometry, and approach development theory. Whatever approach the experts take, at least, to this day, in practice, there are still many educators who place the status of a student’s intelligence as “intellectually intelligent”. As a result, services for optimizing the intelligence of students other than intellectual intelligence tend to be neglected. So, here is the problem, which in many ways is the focus of this research. The method used in this research is a comparative study , library research, involving various points of view of experts, so that a comprehensive conclusion is produced on how to organize and optimize the multiple intelligences of students, without privileging one of the intelligences possessed by students from other intelligences. Which he has. Thus, the expected result of this research is “students will get the same appreciation from each other, from their teachers and/or educator